Studi Interaksi Obat Antihiperlipidemia Pada Pasien Rawat Jalan RSUD Dr. M.M. Dunda Limboto - Rahma Hasan (Tinctura, 2021)
Hyperlipidemia is an abnormal lipid condition of metabolism which is characterized by increasing the level of blood lipid. Hyperlipidemia is often followed by other diseases. Therefore, the treatment of hyperlipidemia is often combined with other drugs and potentially increases the occurrence of drugsinteractions. This study aimed to identify the severity of antihyperlipidemic drugsinteractions to the outpatients at Dr. M.M Dunda Limboto Regional PublicHospital on January to March 2018.This research was included in the observation (survey) research, the type of research was the analytic survey and the data was obtained retrospectively. The type of data analysis was univariate analysis and the data was managed theoretically using the guidelines of Stockley Drug Interactionand drugs.com application review. Of the 170 prescription sheets that met the inclusion criteria, 67.65 % were potentially triggered the drugs interactions and 32.35 % had no drugs interactions. One of Antihyperlipidemic drug was often prescribed and mostly generated the interactions was simvastatin (64.12 %). Of the 170 prescriptions, 209 cases of severity of drugs interactions were found, with minor severity of 27.27 %, moderate severity of 47.85 % and major severity of 24.88 %. Hiperlipidemia merupakan suatu keadaan ketidaknormalan metabolisme lipid yang ditandai dengan adanya peningkatan kadar lipid dalam darah. Hiperlipidemiasering diikuti dengan penyakit lain. Sehingga pengobatan hiperlipidemia seringdikombinasikan bersama obat lain dan berpotensi meningkatkan terjadinyainteraksi obat. Penelitian ini bertujuan untuk mengidentifikasi tingkat keparahaninteraksi obat antihiperlipidemia pada pasien rawat jalan RSUD Dr. M.M DundaLimboto periode Januari sampai Maret 2018. Penelitian ini termasuk penelitian observasi (survei), jenis penelitian survei analitik dan data diambil secara retrospektif. Jenis analisis data adalah analisis univariat dan data dikelola secara teoritik menggunakan Stockley Drug Interaction dan review aplikasi drugs.com. Dari 170 lembar resep yang memenuhi kriteria inklusi, diperoleh 67,65 % berpotensi mengalami interaksi obat dan 32,35 % tidak mengalami interaksi obat. Antihiperlipidemia yang sering diresepkan dan paling besar menimbulkan interaksi obat adalah simvastatin (64,12 %). Dari 170 lembar resep, ditemukan 209 kasus tingkat keparahan interaksi obat, dengan tingkat keparahan minor sebesar 27,27 %, tingkat keparahan moderat sebesar 47,85% dan tingkat keparahan mayor sebesar 24,88 %.